Our Battle for the Human Spirit : Scientific Knowing, Technical Doing, and Daily Living - Vanderburg, Willem H. (Book collections on Project MUSE., 2016)
"Western society has become saturated with scientific and technological modes of thinking that impact our lives and our relationships. Expanding social inequality, the use of social media and the rise of mental illnesses such as anxiety and depression are manifestations of this shift in our civilization. Our Battle for the Human Spirit is a comprehensive probe into what is happening to human life in the beginning of the 21st century. It explores how culture, experience, and symbolization have been replaced by scientific, discipline-based, approaches. Willem H. Vanderburg argues that these approaches are inadequate in understanding the complexity of human lives and societies. In order to transcend these limits, Vanderburg calls for the reintegration of culture and symbolization into our daily lives."--